FENTON PROCESS OPTIMIZATION IN THE TREATMENT OF LANDFILL LEACHATES LIXIVIATED - Valderrama, Medina (2016)
In this study Fenton process was optimized in the treatment of landfill leachates “Aguas de las Virgenes”, Huancayo-Perú. The parameters tested were BOD5 , COD, alkalinity, hardness, pH, conductivity, total solids, turbidity, Pb and Cd. Samples were treated in a system of jars with stirring and to optimize the application values the Box – Behnken design and response surface methodology were used. The values of optimal concentrations were determined in two seasons: rainy seasons (pH = 3.19, 1645.55 mg/L of FeSO4 and 1096.55 mg/L of H2 O2 ) and dry seasons (pH = 3.26, 1788.61 mg/L of FeSO4 and 1180.83 mg/L of H2O2). The optimal reaction time was 20 minutes for both seasons. The Biodegradability indicator was 0.568 and 0.329 in rainy seasons and dry seasons, respectively, with a near elimination of 42% of the COD in both periods. Fenton process is an effective alternative for treatment persistent substances in leachates and can be applied post treatment.